Is Cognitive Impairment a Risk Factor for Post-Stroke Depression? A Meta-Analysis Study - Dinda Ika Pratiwi; Didik Tamtomo; Bhisma Murti (Journal of Epidemiology and Public Health, 2019)
Background: Depression is a psychiatric complication of stroke that often occurs and had a negative impact. Every year, 15 million people who experience strokes globally are at risk of developing post-stroke depression. Cognitive disorders are often associated with the presence of post-stroke depression. Understanding of risk factors for post-stroke depression can help in clinical identification and provide early intervention to improve stroke rehabilitation better. Therefore, it is very important to identify patients at risk for depression. This study aims to analyze cognitive impairment factors in the incidence of post-stroke depression.Subjects and Method: The meta-analysis was conducted from Pubmed, Science Direct, and Springer Link databases using "stroke", "depression", "post-stroke depression AND risk factor" keywords. The article chosen was an article published from January 1, 2009 to September 30, 2018. The data were analyzed using RevMan 5 program.Results: 6 studies consisting of 3140 patients were selected for this study. The results of a meta-analysis showed that cognitive impairment was a risk factor for post-stroke depression. Cognitive disorder was positively and significantly associated with post-stroke depression (OR = 1.24; 95% CI= 1.03 to 1.49; p = 0.02).Conclusion: Cognitive disorder is a risk factor for post-stroke depression.Keywords: depression, post-stroke, cognitive impairment, risk factor, meta-analysisCorrespondence: